ANALYSIS OF COOPERATION, ADAPTATION, EXPERTISE, AND COMMUNICATION EFFECTS ON SATISFACTION AND LOYALTY OF TELKOMSEL DISTRIBUTOR PARTNERS IN PADANG BRANCH - Wira Pratiwi Asril; Syafrizal (Ikatan Dosen Menulis, 2021)
This paper aims to clarify the relationship between cooperation, adaptation, expertise, and communication affecting customer satisfaction and loyalty in B2B environment. We use purposive sampling method and collect primary data: documentation and questionnaire as the media of data collection. The partial least square regression become the technique of analysis to test the probabilities of influences (direct/indirect) to asses the validity and realibility for outer model and structural model. The relationship quality aspects of telecommunication service (communication and expertise) positively related with customer loyalty which is mediated trough customer satisfaction. The study is one of the few empirical investigations into marketing relationship in B2B concept, based on cooperation, adaptation, expertise, communication and examining the mediating effect of customer satisfaction on customer loyalty. This study suggest that in developing country like Indonesia, communicatian on social media and celebrity endorsement more efficient in regional, but in district area we suggest that focus on salesman training (competences) and economy incentive for partners.